Impact Analysis of a Lattice Structure Based Design of Motorcycle Helmet Liners Using Finite Element Modelling - Chanthiran, Nagulan; Subramanian, S. Kanna (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The fact that the number of motorcycle accidents is increasing in Malaysia means there is an urgent need of high-quality helmet designs that could offer better protection of head injuries caused by intense type of collision. In this research, the finite element analysis or FEA in ANSYS Workbench used to study the protective behavior of the foam-filled lattice core sandwich structure motorcycle helmet as compared to the traditional expanded polystyrene (EPS) liner structure of a motorcycle helmet. The study methodology entails extensive three dimensional finite element modeling of the traditional, as well as lattice core-filled helmet design including significant assignment of material properties, meshing, and boundary conditions that allow full three dimensional finite element modeling simulation of a realistic, three dimensional, 5 m/s, linear, side-region impact condition with dynamic loading, or appropriate ligament modeling and characteristics of the headform. The results of the simulation proved the excellent performance of the lattice core-filled helmet design a total of 75.9 percent decrease of deformation (0.19415 m to 0.046752 m), 97.9 percent decrease of equivalent elastic strain (2.2006 m/m to 0.046752 m/m), and much better stress management where stress dissipated fast when it reaches a peak equivalent stress of 132.92 MPa and quickly reduced against the sustained 16.176. Foam-filled lattice core helmets demonstrate significant enhancements in motorcycle crash protection through superior energy absorption, structural integrity, deformation resistance, and stress dissipation, thereby establishing a quantitative foundation for advancing future helmet safety standards.